Effect of Tamoxifen Drug on Testes of Albino Male Rats (Medico Legal Update, 2020)
This study was conducted to evaluate the negative effects of Tamoxifen (TAM) on Testis tissues andspermatogenesis. Use for this purpose forty male of mature albino rats were divided into 4 equal groups, 3groups were administrated different doses (30, 40, 50) mg/kg b.w of TAM for 10 weeks as well as controlgroup administrated with physiological solution (normal saline 0.9%). Histopathological examination oftestes tissues in TAM groups showed histological changes that increased with the increased dose comparedto control group include degeneration change were appeared as atrophy, deformity and destruction of theseminiferous tubules, congestion of blood vessels in the interstitial tissue and many seminiferous tubules,Also the results showed a significant different in the numbers of spermatogonia, primary spermatocytescells and spermatiods. As noted in the results, the higher the dose, the lower the sperm production, andconsequently the tissue injury increases.